PERAN MAHASISWA/I PKM UHN MEDAN DALAM PENGELOLAAN SAMPAH UNTUK PENDIDIKAN LINGKUNGAN DI SMA NEGERI 2 TEBING TINGGI - Bangun; Patrick Kyrie Sihombing; Anita Yohanna Manurung; Widya Lastiarma Pardede; Nelinda Kristauli (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
Finding out how PKM UHN Medan students contribute to waste management for environmental education at SMA Negeri 2 Tebing Tinggi is the goal of this essay. Descriptive approaches are employed in a qualitative approach. The factual conditions that exist in the field are directly described using this method. Documentation, interviews, and observation are used to gather data. Qualitative data analysis involves reducing, presenting, and extracting inferences from data. The data analysis results demonstrate that kids may contribute to keeping the school environment clean. Students’ active participation in fostering mutual cooperation to keep the school environment clean serves as evidence of this.